Assessing the interactions of metal nanoparticles in soil and sediment matrices – a quantitative analytical multi-technique approach. Issue 1 (19th December 2017) - El Hadri, Hind; Louie, Stacey M.; Hackley, Vincent A.
Abstract : Fate and behavior of engineered nanomaterials entering the environment are highly influenced by their interactions with natural particles. Abstract : The impact and behavior of engineered nanomaterials (ENMs) entering the environment is an important issue due to their growing use in consumer and agricultural products. Their mobility and fate in the environment are heavily impacted by their interactions with natural particle components of saturated sediments and soils. In this study, functionalized gold nanoparticles (AuNPs – used as model ENMs) were spiked into complex solid-containing media (standard soils and estuarine sediment in moderately hard water). AuNPs were characterized in the colloidal extract (<1 μm) following centrifugal separation of the non-colloidal phase, using different analytical techniques including asymmetric-flow field-flow fractionation and single particle inductively coupled plasma mass spectrometry. Attachment of functionalized AuNPs to the soil particles did not significantly depend on their concentration or surface coating (citrate, bPEI, PVP, PEG). Similarly, UV degradation of coatings did not substantially alter their recovery. Conversely, the presence of natural organic matter (NOM) is a key factor in their adhesion to matrix particles, by decreasing the predicted influence of native surface chemistry and functional coatings. A kinetic experiment performed over 48 h showed that attachment to soil colloids is rapid and that hetero-aggregation is dominant. These results suggest that transport of ENMs away from the point of discharge (or entry) could be limited in soils and sediments, but additional experiments under more realistic and dynamic field conditions would be necessary to confirm this more generally. Transport properties may also differ substantially in matrices where NOM is largely absent or otherwise sequestered or when dissolution of ENMs is an important factor.